Hydrogeochemical survey of CO2 geological leakage using noble gases: Application to the Furnas Caldera (Azores, Portugual) - Greau, Claire (2012)
Significant natural CO2 emissions have been measured across the caldera of Furnas (São Miguel Island, Azores) allowing us to consider the area as a CO2 leakage analogue. During two field trips, we have collected twenty springs in purpose to measure CO2 contents (Dissolved Inorganic Carbon and "13C) and noble gas isotopic compositions (He and Ne) and for seventeen water samples, major ions chemistry. The corrected 3He/4He ratios (normalized to air ratio RA) range from 1.46 to 5.17, the carbon contents (DIC) range from 0.57 to 41,41 mmol/l and most of the waters have a "13C about -4 ‰. With field observations and waters chemistry, we have characterized seven different types of water springs through the caldera, resulting from various mixing rates between three sources : soil equilibrated meteoritic water, gas emanations (CO2, He…) from a magmatic intrusion and hydrothemal waters coming from a shallow depth aquifer. Saturation indexes and geothermometers indicate a trachytic aquifer at a temperature of about 145°C. In order to confirm that noble gases are good tracers of CO2 leakage, we are building a first mixing model using noble gases and carbon isotopes and a second one based on major ions chemistry with CHESS hydrochemical modelling software. Preliminary mixing models seem to be consistent thus confirming that noble gases can be used as tracors of CO2 leakage.